Wax Lipids from Leaf Surfaces of Some Common plants of Malaysia - Abas, M. Radzi; Simoneit, Bernd R.T. (Universiti Putra Malaysia Press, 1998)
Epicuticular wax lipids from leaves of some common plant species found in the Klang Valley, Malaysia were extracted into dichloromethane for analysis. Extracts were separated into hydrocarbon, carboxylic acid, ketone and alcohol fractions. The fractions after derivatization were then subjected to gas chromatographic (GC) and gas chromatography-mass spectrometric (GC-M5) analyses. The wax yield was highest for Mestta ferrea while the lowest yield was obtained from Eugenia gran dis. In most species studied the m~or n-alkane was found to be hentriacontane (C31 ), followed by tritriacontane (C,,) and nonacosane (C",) , respectively. The n-alkanes exhibit a saw-tooth pattern which is characteristic of a biogenic origin. A strong even-to-odd carbon number predominance is observed for both the n-alkanoic acids and 1)alkanols. Only traces of mainly B-sitosterol were detected in some of the species. The triterpenoids and triterpenes were mostly found in the wax of Mesua ferrea with «- and p-boswellic acids as the major components and minor amounts of «- and p-amyrin. Other biomarkers identified were «and p-amyrones, friedelin, friedelanol, friedelane, olean-12-ene, taraxerene, squalene, dihydronyctanthic acid, dihydroroburic acid and dihydrocanaric acid. This study has shown that the distribution of n-alkanes is a function of the ambient temperature.